CONSTITUTIONAL BASIS FOR THE CIVIL RIGHTS OF ILLEGITIMATE CHILDREN - Nurhayati, Bernadeta Resti (Pattimura Law Journal, 2017)
The specification of children into "legitimate children" and "illegitimate children" is well-known legally and socially. Illegitimate children suffer discrimination because of their status. In law, they only have their mothers and mother's family. Although there has been a Constitutional Court Decision No. 046 / PUU-VIII / 2010, but it does not automatically raise the dignity of illegitimate children. On the other hand Law No. 24 of 2014 has made the children who were not born from a marriage by religion lose their rights to be recognized. This paper was aimed to find the constitutional basis for the civil rights of illegitimate children as the basis to provide the civil rights for illegitimate children so that their civil rights are protected.The method used in this paper was normative.Based on the review, there is a constitutional basis to provide the protection to the civil rights of illegitimate children.